An Overview of Project Management - JAIN, DR MANJULA (The journal of contemporary issues in business and government, 2021)
Project management requires a company's capital to schedule and coordinate a particular mission or responsibility to perform. This may be a one-time initiative or constant operation, and managed resources include employees, finance, technologies and intellectual property. Project management is also related to the areas of architecture and design and later to healthcare and IT, which usually require a complex series of parts to be finalized and assembled to produce a workable product. Project management is mostly conducted by project managers to help identify project priorities and objectives and decide whether and who are to complete the different project components. They also produce quality controls to guarantee that products that are completed follow a certain requirement. This review article discussed the fundamentals of project management including the importance of project management, core components of project management and the iron triangle of project management.